1989
DOI: 10.1051/rnd:19890503
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative inhibitory influence of porcine cumulus cells upon the maturation of pig and cattle oocytes in vitro

Abstract: Summary ― Porcine cumulus oocyte complexes (COCs) were cultured together in 10-)ii droplets of culture medium. When 10 COCs were cultured for 24 h, germinal vesicle breakdown (GVBD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…As described in our previous study (Petr et al, 1989), porcine cumulus cells produce at least one factor quantitatively inhibiting germinal vesicle breakdown (GVBD) in pig oocytes. This inhibitory factor acts indirectly on oocytes through the mediation of cumulus cells.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…As described in our previous study (Petr et al, 1989), porcine cumulus cells produce at least one factor quantitatively inhibiting germinal vesicle breakdown (GVBD) in pig oocytes. This inhibitory factor acts indirectly on oocytes through the mediation of cumulus cells.…”
mentioning
confidence: 77%
“…It was suggested by Dekel and Sherizly (1983) (Dekel et al, 1988) and rabbits (Hosoi et al, 1989) (Petr et al, 1989) and LH is known to induce oocyte maturation through its effect on the somatic follicular periovarian cells (Dekel and …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we described previously (Petr ef al, 1989;Petr et al, 1991) (Petr et al, 1989;Petr et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have demonstrated the presence of a factor produced by cumulus cells from fully grown porcine oocytes, which inhibits GVBD in fully grown pig and cattle oocytes (Petr et al, 1989). This factor is released into the culture medium and its inhibitory effect can be overcome by the addition of LH, heparin or by the transient exposure of oocytes to dbcAMP (Petr et al, 1991).…”
mentioning
confidence: 96%